Rational engineering unlocks the therapeutic potential of WHP1: A revolutionary peptide poised to advance wound healing - Patcharin Khajornpipat; Onrapak Reamtong; Ratchaneewan Aunpad (PLoS ONE, 2025)
Treatment of chronic or non-healing wounds has faced a considerable clinical challenge and impose several detrimental effects on individuals, society, the healthcare system, and the economy. Bioactive peptides have been employed to accelerate wound healing in active wound treatment efficiently and effectively. In the current study, a novel wound-healing peptide, WHP1, was designed from 23 existing wound-healing peptides by a rational template-assisted approach. It demonstrated the ability to enhance migration and proliferation of human keratinocyte cell lines (HaCaT) without exhibiting cytotoxic effects on human red blood cells and HaCaT cells. By quantitative proteomic analysis, WHP1 exerted a multifaceted role on diverse cellular processes in human keratinocyte. Notably, it increased the expression of intracellular proteins of HaCaT cells involved in cell cycle regulation and focal adhesion, including centromeric histone H3 variant CENPA, ubiquitin-conjugating enzyme E2 C, thyroid receptor-interacting protein 6, and ribosomal components essential for cell adhesion and migration. WHP1 upregulated the key enzyme glyceraldehyde-3-phosphate dehydrogenase, orchestrating metabolic biosynthesis particularly glycolysis, cell cycle regulation, and cytoskeletal processes. An intriguing observation was the antioxidant activity of WHP1, protecting cells from reactive oxygen species-induced senescence. This is consistent with the upregulation of GAPDH expression and reduction of histone H2A.J levels. WHP1 also stimulated macrophages to secrete transforming growth factor-β (TGF-β), a crucial growth factor necessary for the remodeling phase of wound healing. This investigation highlighted the feasibility of rational design to create novel wound-healing peptides. Such advancements hold promise for improving patients’ quality of life and elevating the standard of care in contemporary healthcare.